Routing vehicles through cross-docking facility for third party logistics service providers - Birasnav, M.; Kalaivanan, S.; Ramesh, A.; Tibrewala, Rajendra (International Journal of Operational Research, 2020)
This study focuses on a specialised vehicle routing problem (VRP) to transport matchboxes from manufacturing companies to retailers through a cross-dock (cross-docking facility) operated by a third party logistics service provider. Three processes (unloading, consolidating, and loading) are carried out at a cross-dock for completely avoiding or keeping inventory for a very short time. The specialised VRP, addressed in this paper, consists of multiple suppliers (each supplier can produce different brands of products for any number of customers) and multiple customers (each customer can receive orders from any number of suppliers). A mixed integer linear programming model has been developed to solve this kind of NP-hard problem. The objective of this model is to minimise total cost incurred in picking up and transporting the matchboxes from the manufacturers to cross-dock, consolidating matchboxes at cross-dock, and in transporting and delivering the matchboxes to the customers. This study also proposes an effective heuristic procedure to solve the same problem and compares the solution obtained using the heuristic procedure to the optimal solution obtained using the exact method. The findings show that the heuristic method, proposed by us, generates near optimum solutions using significantly less computational time than the exact method.
Keywords: NP-hard; consolidating; cross-docking; dept.mgt; heuristic; logistics service provider; multiple customers; multiple suppliers; peer-reviewed; vehicle routing

Recruiting and Retaining the Genius Generation for Virtual Teams from a Generation Z Perspective - McGraw, Laquita; Stewart, Carol (International Journal of Business Research & Information Technology (IJBRIT), 2020)
The concept of a virtual team is expanding as its application is growing with multiple generations in the workforce. A virtual team is now a significant issue in the 21st century because there are currently five generations in the workforce. To lead a multigenerational virtual team, employers must understand a new generation that is entering the workplace. Although Generation Z will bring new characteristic to the workforce, leadership styles must transform to accommodate a newer generation's expectations. This study explores leadership styles to support virtual teams and a new generation. There exist only a few qualitative studies on virtual teams in today's domestic workforce. The researchers wish to gain knowledge of which leadership style works for a virtual team from the perspectives of Generation Z.
Keywords: GENERATION Z; GENIUS; Generation Y; Generation Z; LEADERSHIP; TEAMS; VIRTUAL communities; VIRTUAL work teams; Virtual team; dept.mgt; leadership; peer-reviewed

Leadership and Corporate Social Responsibility in Sports: If You’re Not First, You’re Last - Stewart, Carol; Marciniec, Sheryl; Joyner-McGraw, Laquita; Han, Seungmin (International Journal of Business and Public Adminstration, 2020)
Keywords: dept.mgt; peer-reviewed

Characteristics of Effective Trade Secrets and Confi dential Information Policies: Guidance from Labor Arbitration Cases - Ross, William H.; Franklin, Danny (Labor Law Journal, 2020)
In an effort to craft recommendations to managers regarding effective confidential information policies, the present paper reviewed 88 published grievance arbitration cases involving proprietary information, trade secrets, and confidential information. Most cases dealt with the application of managerial discipline for employee violations of company polices and collective-bargaining provisions. Themes that emerged included: the importance of a Management Rights clause (as well as specific Misconduct clauses and policies), clauses that address changing business conditions (such as subcontracting and new technology), employee insubordination, theft, falsification, conflict of interest, and the need for training. Additionally, arbitrators often considered specific laws that apply in health care, cable television, and telecommunications industries. Finally, several mitigating factors were noted such as: having permission from a supervisor to access confidential information, safety, and whistleblowing concerns. By attending to factors that influence arbitrator decision making, managers and their attorneys can use these identified factors to create better policies and negotiate robust collective bargaining provisions.
Keywords: Arbitration; Business And Economics--Labor And Industrial Relations; Collective bargaining; Competition; Competitive advantage; Conflicts of interest; Discipline; Employees; Espionage; Fair & Accurate Credit Transactions Act 2003-US; Information policies; Intellectual property; Labor law; Law; dept.mgt

Advice-Taking in Ethical Dilemmas - Franklin, Danny; Guerber, Amy J. (Editorial Policy, 2020)
Keywords: dept.mgt; peer-reviewed

The Effect of Higher Education on Youth Unemployment in European Regions During a Period of Economic Instability - Hermannsson, K.; Scandurra, R.; Graziano, M. (Journal of Education Finance, 2020)
This paper examines the impact of higher education on youth unemployment. Following the 2008 financial crisis, youth unemployment returned to the fore as a serious concern among policy makers in Europe. A crucial difference from previous recessions is that this time around supply of higher education opportunities was much higher than in the 1980s, and indeed higher education participation rates grew rapidly in many regions during this period. Drawing on previous work on youth unemployment and the economic impacts of education we identify a variety of channels through which higher education is likely to influence youth unemployment. We examine this issue using a macro-panel of European regions for the period 2002-2012. This decade was characterized by variation in economic activity and higher education rates. Our results suggest that expansion of higher education during this period had a mitigating effect on youth unemployment and not recognizing this external benefit of education risks underestimating the effects of macroeconomic shocks on young people. © 2020, University of Illinois Press. All rights reserved.
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

A comparison of two multilingual meeting systems - Aiken, Milam; Park, Mina (International Journal of Computers & Technology, 2020)
Keywords: Google Translate; dept.bis; dept.mgt; peer-reviewed

Increasing demand and a tradeoff between speed-cost efficiencies and total profits - Lee, Minjae (Academy of Management Proceedings, 2020)
Keywords: dept.mgt

Developing the elusive construct of speed-cost efficiency - Lee, Minjae; Mahoney, Joseph T. (Academy of Management Proceedings, 2020)
Keywords: dept.mgt

A temporal analysis of employees’ situational work motivation and well- being - Wang, Zheni; Panaccio, Alexandra Joelle (Academy of Management Proceedings, 2020)
Keywords: dept.mgt

Thinkubator Approach to Solving the Soft Skills Gap - Stewart, Carol; Marciniec, Sheryl; Lawrence, Denval; Joyner-McGraw, Laquita (American Journal of Management, 2020)
Keywords: dept.mgt; peer-reviewed

Uncovering Relations Between Leadership Perceptions and Motivation Under Different Organizational Contexts: a Multilevel Cross-lagged Analysis - Gagné, Marylène; Morin, Alexandre J. S.; Schabram, Kira; Wang, Zhe Ni; Chemolli, Emanuela; Briand, Mélanie (Journal of Business and Psychology, 2020)
Surprisingly scant research has adequately examined directional influences between different perceptions of managerial leadership behaviors and different types of work motivation, and even fewer studies have examined contextual moderators of these influences. The present study investigated longitudinal and multilevel autoregressive cross-lagged relations between perceptions of transformational, transactional, and passive-avoidant leadership with autonomous motivation, controlled motivation, and amotivation. Multilevel longitudinal models were estimated on data from 788 employees, nested under 108 distinct supervisors, from six Canadian organizations. Results revealed that perceptions of leadership behaviors predicted changes in motivation mostly at the collective level and that some of these relations changed as a function of whether organizations had recently faced a crisis. Collective perceptions of transformational leadership were related to increased collective autonomous and controlled motivation, while individual controlled motivation was related to increased individual perceptions of transactional leadership. In organizations facing a crisis, individual perceptions of transactional leadership were related to decreased individual controlled motivation, while collective perceptions of transactional leadership were related to increased collective autonomous motivation and decreased collective amotivation. In organizations not facing a crisis, collective perceptions of transactional leadership were related to decreased collective autonomous motivation. Implications for theory and practice are discussed.
Keywords: Autonomous motivation; Multilevel modeling; Transactional leadership; Transformational leadership; dept.mgt; peer-reviewed

Family Law and Practice - Luppino, Grace A.; Miller, Justine FitzGerald (Legal practice guides, 2020)
For courses in family law for students in paralegal studies programs, broader legal studies programs, and those majoring in criminal justice, social work, and education. Connecting theory, history, and practice in family law Family Law and Practice prepares students to enter the workplace with a firm grasp of family law and procedural components of family law practice. To meet this challenge, the authors have divided the 5th edition into two parts: the first introducing the principles of family law and the second translating theory into practice. The new edition also addresses changing views on marriage, spousal roles, children’s status in the family, and even what constitutes a family. It also adds cases, statutes, and legal forms from a variety of US states to engage students across the country.
Keywords: Domestic relations; Handbooks, manuals, etc; United States; United States; Legal assistants; dept.mgt; faculty_collection